The Distinctive Evolution of orfX Clostridium parabotulinum Strains and Their Botulinum Neurotoxin Type A and F Gene Clusters Is Influenced by Environmental Factors and Gene Interactions via Mobile Genetic Elements - Smith, Theresa J.; Williamson, Charles H. D.; Hill, Karen K.; Johnson, Shannon L.; Xie, Gary; Anniballi, Fabrizio; Auricchio, Bruna; Fernández, Rafael A.; Caballero, Patricia A.; Keim, Paul; Sahl, Jason W. (Frontiers in Microbiology, 2021)
Of the seven currently known botulinum neurotoxin-producing species of Clostridium, C. parabotulinum is the species associated with the majority of human botulism cases worldwide. The neurotoxins they produce are diverse, with over 20 subtypes currently represented. The toxin genes are associated with one of two toxin gene cluster types (ha+ or orfX+) and may be located within the chromosome or large conserved plasmids. Genomic analyses reveal C. parabotulinum to be a diverse species, with multiple clades that may or may not contain the same neurotoxin genes and, conversely, the same toxin genes may be located within multiple C. parabotulinum genotypes. The independent evolutions of bacteria and neurotoxins are dependent on dispersal of strains via spore movements and interactions of mobile genetic elements among these strains that impart new or modified characteristics. The interplay of these mobile elements, including homologous gene transfers on a macro scale and mutations/recombination events on a genetic level, has resulted in the diversity of organisms and neurotoxins that is present today. Examination of a subset of botulinum neurotoxin-producing bacteria, C. parabotulinum that contain orfX+ bont/A and bont/F genes, illustrates this diversity. In order to better understand the mechanisms behind genetic transfer, genes that are associated with specific toxin gene clusters within the plasmids or the chromosome, such as lycA, arsC1, pulE, and HepA/SNF2 genes, are discussed.